Associating Designed Information and Novelty with Purchase Intentions for Product Displays in Fashion Apparel Stores - Saini, Shweta; Bansal, Sanjeev (Indian Journal of Marketing, 2023)
Purpose : This paper aimed to synthesize designed information, novelty, perceived usefulness, involvement, attitude, and purchase intentions. Scholars developed a conceptual model and hypotheses to reinforce the literature review on these factors. Methodology : This study used modified scales from earlier studies that have been published in journals. With 510 respondents, the data were gathered using the snowball technique. To assess the data set, structural equation modeling was employed. Findings : The findings of this study indicated a significant relation between designed information and novelty with perceived usefulness and involvement. Furthermore, the relationship between perceived usefulness and involvement as mediators with attitude toward product display was investigated and found to be significant. Practical Implications : The study’s primary conclusion was that consumers’ intentions to buy clothing in physical stores may be influenced by the way different conceptions are related to one another. The findings of this research offered valuable insights to retailers, visual merchandisers, and store managers regarding the significance of designed information and novelty in product displays within apparel brick-and-mortar stores, ultimately leading to purchase intentions. This research paper pioneered the study combining product display constructs. Originality : This study is noteworthy because of its findings, which linked planned information, novelty, perceived usefulness, involvement, attitude, and purchase intentions, expanding the product display stimulus-organism-response (S-O-R) framework. Specifically, it identified perceived usefulness, involvement, and attitude toward product displays as a mediator in linking designed information, novelty, and purchase intentions.